"Baptismus barbarorum" oder christliche Initiation in der Neuen Welt Amerika (16. Jahrhundert) - Sievernich, Michael 1945- (Rechtsgeschichte, 2013)
The contribution raises the question of baptism as Christian initiation in the context of early modern European expansion and mission of the New World America. Based on narrative reports as well as legally, canonistically and theologically normative sources of the 16th Century, with emphasis on the contemporary synods and scholarly disputes, the article unfo lds three perspectives: A first discusses the ritual inclusion through baptism based on the different baptismal practices of the time and the controversies around the theological and canonistical minimum requirements; the second perspective focuses on the cognitive instruction of the neophytes, based on the pre-and postbaptismal instruction and the linguistic tools such as catechisms in indigenous languages; the third perspective, finanally, treats the multiple participation on the basis of the rights and obligations resulting from the acceptance of Christian faith. The multi-perspective view of the theory and practice of baptism in early modern Spanish America shows a complex context of a ritual, cognitive and participatory level, which was reflected in prescriptive and argumentative tracts. The multifaceted aim of baptism was the voluntary change of religion, associated with the theological, andiropological and legal recognition of the indigenous individual, even if the participation rights in the new status had to be obtained.